2015
DOI: 10.1002/vnl.21470
|View full text |Cite
|
Sign up to set email alerts
|

The toughness and morphology of (chlorinated poly[vinyl chloride])/(methyl methacrylate‐butadiene‐styrene) blends

Abstract: A series of methyl methacrylate‐butadiene‐styrene (MBS) graft copolymers were synthesized via seeded emulsion polymerization techniques by grafting styrene and methyl methacrylate on poly(butadiene‐co‐styrene) (SBR) particles. The chlorinated poly(vinyl chloride) (CPVC)/MBS blends were obtained by melting MBS graft copolymers with CPVC resin, and the effect of the core/shell ratio of MBS graft copolymer and SBR content of CPVC/MBS blends on the mechanical properties and morphology of CPVC/MBS blends was studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…This polymer is produced through a post-chlorination process that raises the chlorine content from 57.4% in PVC to 70% in CPVC [3]. This modification is intended to raise the glass transition temperature T g of the base resin from 95°C to 115-135°C and improves its mechanical characteristics at elevated temperatures [4]. The CPVC pipes have higher temperature and pressure rating than PVC pipes, making them suitable for hot water delivery systems and other applications requiring higher temperatures and pressure ratings [5].…”
Section: Introductionmentioning
confidence: 99%
“…This polymer is produced through a post-chlorination process that raises the chlorine content from 57.4% in PVC to 70% in CPVC [3]. This modification is intended to raise the glass transition temperature T g of the base resin from 95°C to 115-135°C and improves its mechanical characteristics at elevated temperatures [4]. The CPVC pipes have higher temperature and pressure rating than PVC pipes, making them suitable for hot water delivery systems and other applications requiring higher temperatures and pressure ratings [5].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, compared to other modifiers, the MBS modifier, to some extent, can simultaneously possess the characteristics of the improved toughness and retained transparency of the PVC blends [8]. It has been demonstrated that MBS particles with the diameter <100 nm could provide the PVC matrix with excellent transparency, while the particles with the diameter >200 nm can provide the matrix with outstanding toughness [9]. Therefore, the traditional MBS latex particles with a narrow size distribution are not desirable to meet those demands.…”
Section: Introductionmentioning
confidence: 99%